THE LIFE TRANSITIONS OF HIGH PERFORMANCE ATHLETES RETIREMENT FROM SPORT - Hatamleh, Mazin R. (European Scientific Journal, ESJ, 2013)
﻿﻿﻿The purpose of the study was to examine the transition experience of Jordanian national athletes retirement from the sport. Also, to investigate reasons of retirement, difficulties faced by athletes during transition and strategies used to cope with retirement. Subjects were (N=53) athletes (M=33, F=19), representing the Jordan National teams in different sports. Data was collected through the use of the Athlete Retirement Questionnaire (ARQ), developed by (Sinclair & Orlick, 1993), which include (34) items divided into three variables ( reason of retirement, difficulties during transition, and coping strategies) and Personal Characteristics. Descriptive static, mean, standard deviation, percentage, and t. test were used to analyze the results. Results showed that reasons of retirement was due to athletes struggles with coaches, problem with sport federation, athletes experienced difficulties during retirement, missing social aspect of sport, lack of self- esteem, keeping feelings to self. Speaking with a friend who listens, were used as coping strategies by athletes. Athletes experienced stress during and following retirement. Finally, the quality of the sports career termination process depends on the freewill of athletes career termination. The study provides unique insight into the psychological effect of forced retirement from the sport. Therefore, it is recommended that more attention should be paid when to prepare and assist athletes during their transition to retirement, and, for the Jordanian Olympic committee to establish an (Athletic Service Center) to assist voluntaries athletes during their transition to career termination, and provide help after retirement.